KONDISI SOSIAL EKONOMI MASYARAKAT PANTE LHONG TERDAMPAK BENCANA HIDROMETEOROLOGI DI KABUPATEN BIREUEN - Nailiza Herlia; Wahyudi; Muslihin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Hydrometeorological disasters in the form of floods have had significant impacts on the social and economic conditions of communities in Pante Lhong Village, Bireuen Regency. This study aims to analyze the socio-economic conditions of the community after being affected by hydrometeorological flooding, identify the recovery efforts undertaken by the affected residents, and examine the positive and negative impacts resulting from the disaster. This research employed a qualitative approach using a descriptive research design. The research informants were selected purposively and consisted of community leaders and residents affected by the disaster. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, while the validity of the data was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that hydrometeorological flooding caused substantial changes in the socio-economic conditions of the community, including damage to houses, disruptions to health, education, and livelihoods, decreased income, and damage to productive assets and infrastructure. The affected community undertook various recovery efforts, such as cleaning houses and agricultural land, seeking alternative employment, relying on family support, strengthening cooperation, and utilizing assistance from the government and external organizations. In addition to negative impacts, including economic losses, psychological distress, and temporary displacement, the disaster also generated positive outcomes, such as increased public awareness of disaster mitigation, strengthened social solidarity, and improved soil fertility in certain areas due to sediment deposition. It can be concluded that the recovery of the community's socio-economic conditions requires sustained collaboration among the community, government, and various institutions to enhance resilience against future disasters.